Family Nursing Care Based On Complementary Therapy Using Syzygium Polyanthum In Families With Gout Arthritis - permatasari, chintia ayu; setiyorini, erni; putri, roro dewi; Fernandez, Angelina Da Costa (Health Gate, 2025)
Gout arthritis is a non-communicable disease commonly found in the elderly, characterized by joint pain due to monosodium urate crystal deposition. Its high prevalence in Indonesia is associated with a high-purine diet, low physical activity, and limited knowledge of disease management. Complementary therapy using boiled bay leaves offers a safe and affordable method to reduce uric acid levels. This case study was conducted on four families with elderly members aged 60–75 years suffering from gouty arthritis in the Sananwetan Community Health Center, Blitar City. Nursing care was provided through assessment, nursing diagnosis, planning, intervention, implementation, and evaluation. Interventions included health education on a low-purine diet and administration of 10–15 bay leaves boiled in 200–400 ml of water, consumed once daily for six days. Data collection was performed through interviews, observations, and physical examinations, including uric acid level monitoring. The main nursing diagnoses established were ineffective family health management, chronic pain, knowledge deficit, readiness to improve coping, readiness to enhance knowledge, and impaired family processes. Results showed a reduction in uric acid levels (average 6.2 mg/dl), decreased joint pain, and improved family knowledge and involvement in patient care. This study highlights the effectiveness of integrating family-based health education and complementary therapy using bay leaves in managing gouty arthritis. Family support proved to be an essential factor in successful disease control and quality of care for elderly patients.